Conference Record of the 1999 IEEE Industry Applications Conference. Thirty-Forth IAS Annual Meeting (Cat. No.99CH36370)
DOI: 10.1109/ias.1999.799962
|View full text |Cite
|
Sign up to set email alerts
|

Mobile roof support load rate monitoring system

Abstract: Mobile roof sunwrt (MRS) machines are used as roof .. . . ~ ~~~ suppiirt during pillar rccovery in retreat operations in lieu of wooden posts, cribs, or hydraulic props. A Mine Safely and Hrdlth Administmtion-perniissihle load rate monituring sydrm was developed fnr the hlRS by researchers at the Spokane Research Laboratnry of the Satiunnl Institute for Occupational Safety and Hedth. The system uses a dedicated embedded processor to monitor changes in pressure inside the hydraulic cylinders of the hIRS through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mathematical models for distinguished phases of the roof support operation cycle describing the changes in pressure in the props can be found in 11 . Research on this subject and various analytic approaches can be also found in 12 .…”
Section: E Brzychczy a Trzcionkowskamentioning
confidence: 99%
“…Mathematical models for distinguished phases of the roof support operation cycle describing the changes in pressure in the props can be found in 11 . Research on this subject and various analytic approaches can be also found in 12 .…”
Section: E Brzychczy a Trzcionkowskamentioning
confidence: 99%